The role and development of Bangladesh Jama'at-E-Islami (BJI) with special reference to the Qur'anic concept of al-wasatiyyah - Islam, Muhammad Hedayatul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Al-WasaÏiyyah as a multi-dimensional concept is scholarly acknowledged as a “justly balanced path or balanced approach” of Islam. The term gained popularity and became prominent in Muslim communities and the media after the attacks of September 11, 2001. In the context of contemporary Islamic thought, al-WasaÏiyyah is the counterweight of religious extremism and liberalism. Many liberal Muslim intellectuals and non-Muslim scholars tend to link terrorism and extremism to the existing Islamic movements globally. However, leaders of moderate Islamic movement never approve of a global JihÉd or terrorism against the West, as well as of war against Islam and Muslims by the West. This study aims at investigating the relevance of the concept al-WasaÏiyyah in Bangladesh, addressing the multifarious problems besetting the Muslim world. The Bangladesh JamÉÑat-e-IslÉmÊ (BJI), a contemporary leading Islamic movement in Bangladesh, represents a comprehensive example of a Muslim group in trying to address the prevailing socio-cultural and politico-economic problems which Muslim nations face. This research first examines al-WasaÏiyyah from main sources - the Qur'Én and Sunnah based on the interpretation of early and contemporary scholars' views. Then it analyses opinions and objectives of BJI: organization's policy, ideology, social activities and most importantly political activities involvements in the government policies. In this regard, JamÉÑat's constitution, literatures and various lectures of the top leaders available were also reviewed. In parallel, an exploratory case study (semi-structured interviews) was conducted to measure JamÉÑat's practical activities (practice) with their theory. This study found that the concept al-WasaÏiyyah is used as an important means for an Islamist Movement to revert the ultra-secular polity as well as liberal and extreme views not in favor of Islam. This study concludes that based on the true Islamic teachings, the BJI has the potential not only in promoting a 'Balanced Approach' as championed by Islam but also to develop a social movement based on the worldview of Islam. While achieving this goal, the need for political authority and a grassroots network is central to countering terrorism, extremism and liberalism in Muslim-majority country like that of Bangladesh. However, the critics representing the left-leaning anti-Islamic forces tend to blame BJI for its failure to take a stand against the exploitation and injustices perpetrated on the fellow Muslims of the erstwhile East Pakistan since 1947 until the liberation of Bangladesh in 1971.